Simulation of saturation process in a transuranium disposal facility. Issue 5 (1st February 2016) - Takayama, Yusuke; Iizuka, Atsushi; Kawai, Katsuyuki
Abstract : Bentonite materials have been considered as a candidate material for engineered barriers in transuranium (TRU) waste disposal facilities due to their physical and chemical characteristics. Bentonite materials will be initially compacted and unsaturated. After closing the cavern, the bentonite material will become saturated through exposure to a percolating groundwater. It is therefore important to understand the behaviour of bentonite during saturation, which provides an initial condition of the disposal facilities. This paper explains a mathematical model which can express the saturation process. Subsequently, a series of numerical simulations were carried out. First, the swelling pressure of buffer and backfill was examined to verify the numerical model. It was confirmed that the simulated swelling pressure rises with water absorption, and swelling pressure test results from the literature are shown to be satisfactorily predicted by the numerical model, although these were slightly overestimated. Next, the mechanical behaviour of bentonite materials in a TRU waste disposal facility during the saturation process was examined using soil/water/air coupled finite-element method. Although it is difficult to examine the validity of analysis results because of the difficulty of an extremely long-term measurement, the qualitative behaviour of the saturation process could be inferred.